Role of galactolipid biosynthesis in coordinated development of photosynthetic complexes and thylakoid membranes during chloroplast biogenesis in Arabidopsis. (26th November 2012) - Kobayashi, Koichi; Narise, Takafumi; Sonoike, Kintake; Hashimoto, Haruki; Sato, Naoki; Kondo, Maki; Nishimura, Mikio; Sato, Mayuko; Toyooka, Kiminori; Sugimoto, Keiko; Wada, Hajime; Masuda, Tatsuru; et al.
Summary: The galactolipids monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG) are the predominant lipids in thylakoid membranes and indispensable for photosynthesis. Among the three isoforms that catalyze MGDG synthesis in Arabidopsis thaliana, MGD1 is responsible for most galactolipid synthesis in chloroplasts, whereas MGD2 and MGD3 are required for DGDG accumulation during phosphate (Pi) starvation. A null mutant of Arabidopsis MGD1 ( mgd1 ‐ 2 ), which lacks both galactolipids and shows a severe defect in chloroplast biogenesis under nutrient‐sufficient conditions, accumulated large amounts of DGDG, with a strong induction of MGD2/3 expression, during Pi starvation. In plastids of Pi‐starved mgd1‐2 leaves, biogenesis of thylakoid‐like internal membranes, occasionally associated with invagination of the inner envelope, was observed, together with chlorophyll accumulation. Moreover, the mutant accumulated photosynthetic membrane proteins upon Pi starvation, indicating a compensation for MGD1 deficiency by Pi stress‐induced galactolipid biosynthesis. However, photosynthetic activity in the mutant was still abolished, and light‐harvesting/photosystem core complexes were improperly formed, suggesting a requirement for MGDG for proper assembly of these complexes. During Pi starvation, distribution of plastid nucleoids changed concomitantly with internal membrane biogenesis in the mgd1‐2 mutant. Moreover, the reduced expression of nuclear‐ and plastid‐encoded photosynthetic genes observed in the mgd1‐2 mutant under Pi‐sufficient conditions was restored after Pi starvation. In contrast, Pi starvation had no such positive effects in mutants lacking chlorophyll biosynthesis. These observations demonstrate that galactolipid biosynthesis and subsequent membrane biogenesis inside the plastid strongly influence nucleoid distribution and the expression of both plastid‐ and nuclear‐encoded photosynthetic genes, independently of photosynthesis.